2012
DOI: 10.1245/s10434-012-2252-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10a is Overexpressed in Human Pancreatic Cancer and Involved in Its Invasiveness Partially via Suppression of the HOXA1 Gene

Abstract: The present data suggest that miR-10a is overexpressed in a subset of pancreatic cancers and is involved in the invasive potential of pancreatic cancer cells partially via suppression of HOXA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 34 publications
2
77
0
Order By: Relevance
“…Several miRNAs that were downregulated by Gal-9 treatment have been reported to be associated with cancer cell apoptosis. For instance, miR-10a has been reported to be upregulated in several solid tumors including pancreatic cancer (35) and lung cancer (36). miR-10a targets the phosphatase and tensin homolog (PTEN), and miR-10a promotes the migration, invasion, and growth of non-small cell lung cancer by regulating the PTEN/AKT/ERK signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs that were downregulated by Gal-9 treatment have been reported to be associated with cancer cell apoptosis. For instance, miR-10a has been reported to be upregulated in several solid tumors including pancreatic cancer (35) and lung cancer (36). miR-10a targets the phosphatase and tensin homolog (PTEN), and miR-10a promotes the migration, invasion, and growth of non-small cell lung cancer by regulating the PTEN/AKT/ERK signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have established a pro-proliferative role for this cluster in multiple cancers including pancreatic cancer and acute myeloid leukemia [150][151][152]. This role is consistent with our finding that it positively regulates activation of a TF known for its role in promoting proliferation, particularly in the context of cancer [147].…”
Section: Ap-1supporting
confidence: 91%
“…Overexpression of miR-10a contributes to the enhanced invasiveness in pancreatic cancer through suppression of the HOXA1 gene. 12) Higher expression of miR-10a may be also associated with an adverse outcome in breast cancer. 13) Moreover, it was reported that miR-10a can regulate the proliferation of human cardiomyocyte progenitor cells.…”
mentioning
confidence: 99%